Lingkungan Rumah Berhubungan dengan Malaria pada Ibu Hamil - Susi Lestari (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the relationship between the home environment and malaria in pregnant women. The method used in this study is a quantitative study with a cross-sectional approach. The results showed that more pregnant women had malaria as much as 65.2%, there were standing water as much as 50.0%, there were bushes as much as 54.3%, they did not use wire netting as much as 52.2%, they did not use ceilings as much as 60.9% and not using tight walls as much as 56.5%. In conclusion, a significant relationship exists between the home environment and malaria in pregnant women. Keywords: Pregnant Women, Home Environment, Malaria